2020
DOI: 10.3126/md.v23i2.35821
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Factors in Predicting Organizational Commitment of Nepal Telecom Employees

Abstract: The study intends to assess the 3-dimensional organizational commitment and its effects on socio-demographic factors such as gender, age, and tenure of Nepal Telecom employees. Random sampling method proportionately to the job position level had been harnessed to collect primary data with survey method and ultimately, 322 samples were gathered. Analysis tools t-test, ANOVA, post hoc analysis harnessed to examine the objectives. The study results that age and work experience are significantly associated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As people age, they have additional chances to gain understanding and cultivate the ability to efficiently employ available resources to handle diverse situations. Earlier studies have also revealed a positive relationship b/t age and management skills (Bailey et al, 2020;Jain & Lamichhane, 2020). Similarly, a study found that senior managers exhibited higher levels of self-regulation than younger managers in a study.…”
Section: Extent Of Self-management Skills (Sms)mentioning
confidence: 62%
See 1 more Smart Citation
“…As people age, they have additional chances to gain understanding and cultivate the ability to efficiently employ available resources to handle diverse situations. Earlier studies have also revealed a positive relationship b/t age and management skills (Bailey et al, 2020;Jain & Lamichhane, 2020). Similarly, a study found that senior managers exhibited higher levels of self-regulation than younger managers in a study.…”
Section: Extent Of Self-management Skills (Sms)mentioning
confidence: 62%
“…For instance, the study conducted among Nepal Telecom employees involving 322 respondents assessed Organizational Commitment (OC) and its effects on DF, such as age, gender, and work experience. The study outcome revealed that age and work experience are significantly connected with employee commitment, though the high and low working years of employees show differences (Jain & Lamichhane, 2020). Similarly, studies on school teachers show a managerial role in the lecture theater, institute, and the broader community.…”
Section: Commitment Ability (Ca)mentioning
confidence: 90%